Determination of oxidative stress level and antioxidant enzyme activities in biathlon athletes and sedentary athletes - Birinci, C. (Progress in Nutrition, 2022)
Study Objectives: This study aimed to compare oxidative stress levels and enzyme activities in biathlon skiers and sedentary athletes.